Management of elderly people with Stroke: strategies based on action research - Luna Vitória Cajé Moura; Larissa Chaves Pedreira; Tânia Maria de Oliva Menezes; Nildete Pereira Gomes; Alyne Henri Motta Coifman; Alice de Andrade Santos
ABSTRACT Objective: To elaborate and implement, through an educational intervention with the nursing team of the Emergency Unit, strategies that contribute to the management of elderly people suspected/affected by Stroke. Method: Action research with eighteen nursing professionals working in the Emergency Unit of a reference hospital. The data were collected through five pedagogical workshops and systematized through the thematic analysis. Results: After a situational analysis and identification of the difficulties in the management of these elderly, a synthesis chart was prepared with strategic actions, responsible professionals and perspectives for implementation in the short, medium and long term. Short-term strategies had, for the most part, immediate implementation; the others were agreed on the need for further implementation. Final considerations: The educational intervention allowed the construction of strategies that were implemented or agreed with the management for later applicability, sensitizing the group regarding the importance of the qualification and prompt care in the management of the elderly suspected/affected by Stroke.